Enzymatic Polymerization of PCL-PEG Co-polymers for Biomedical Applications - Figueiredo, Pedro; Almeida, Beatriz C.; Carvalho, Alexandra T. P. (Frontiers in Molecular Biosciences, 2019)
Biodegradable polymers, obtained via chemical synthesis, are currently employed in a wide range of biomedical applications. However, enzymatic polymerization is an attractive alternative because it is more sustainable and safer. Many lipases can be employed in ring-opening polymerization (ROP) of biodegradable polymers. Nevertheless, the harsh conditions required in industrial context are not always compatible with their enzymatic activity. In this work, we have studied a thermophilic carboxylesterase and the commonly used Lipase B from Candida antarctica (CaLB) for tailored synthesis of amphiphilic polyesters for biomedical applications. We have conducted Molecular Dynamics (MD) and Quantum Mechanics/Molecular Mechanics (QM/MM) MD simulations of the synthesis of Polycaprolactone—Polyethylene Glycol (PCL—PEG) model co-polymers. Our insights about the reaction mechanisms are important for the design of customized enzymes capable to synthesize different polyesters for biomedical applications.